Medida socioeducativa de internação e suas interfaces com o esporte e lazer - Oliveira, Ueliton Peres de (2020)
This research is based on the assumptions of the qualitative approach of the exploratory and descriptive type, with the objective of retrospectively analyzing the access to Sports and Leisure of adolescents in compliance with a socio-educational measure of hospitalization. To this end, the research is structured in three chapters/articles that interrelate and seek to elucidate the issue that permeates the present study. The first chapter aimed to highlight the research panorama related to sport and leisure in contexts of socio-educational measures in Brazil. Nine scientific articles and five dissertations were selected by searching CAPES Journals, Scientific Electronic Library Online Database, Google Scholar and CAPES Theses and Dissertations database. The first chapter aimed to highlight the research panorama related to sport and leisure in contexts of socio-educational measures in Brazil. Nine scientific articles and five dissertations were selected by searching CAPES Journals, Scientific Electronic Library Online Database, Google Scholar and CAPES Theses and Dissertations database. The results were treated based on Content Analysis. Through the categories of analysis it was observed that the sports and leisure, when treated as educational paths and objects, provide environments conducive to the positive development of adolescents, although they are designed based on utilitarian and functional logic by the institutions and adolescents. It is concluded that the restricted understanding of adolescents about sport and leisure potential is closely linked to the lack of access to these policies in during their trajectories. In the second chapter, documentary research was carried out in order to understand access to sport and leisure in the trajectory of adolescents in compliance with a socio-educational measure of hospitalization in the State of Mato Grosso and to identify the profile of these subjects. 36 Individual Service Plans (PIA) from seven SocioEducational Service Centers, developed between 2017-2018 and made available by the State Management System for Children and Adolescents, were analyzed – SIPIA/SINASE/MT. The data related to the sports and leisure axes were treated through content analysis. The profile of adolescents portrays the socioeconomic and social vulnerability problems present in the contemporary world. From the analysis categories, there was a limited offer of these care policies in the trajectory of adolescents. It is concluded that, the fulfillment of the socioeducational measure of hospitalization provided greater access to spaces, equipment and sports and leisure contents for adolescents, when compared to their experiences prior to the application of the measure. In the third chapter, an exploratory and descriptive study was carried out with the objective of identifying the spaces, equipment and sports and leisure contents of a municipality in the State of Mato Grosso with a higher incidence of adolescents in compliance with a socio-educational measure of hospitalization in the years 2017 and 2018. The data were made available by the State Management of the System for Children and Adolescents - SIPIA / SINASE / MT. On-site observation was carried out in eight neighborhoods, using predefined analysis categories for field diary records. The results demonstrate the scarce offer of spaces, equipment and content available in these communities, signaling the need for effective policies for primary care for adolescents. In view of this scenario, it is concluded that the lack of access to sports and leisure policies is seen as a risk factor for committing infraction in the context researched, in addition to exposing young people to the same risk when returning to the community.